2017
DOI: 10.1039/c7cp04662f
|View full text |Cite
|
Sign up to set email alerts
|

A novel explanation for the enhanced colloidal stability of silver nanoparticles in the presence of an oppositely charged surfactant

Abstract: The structural behavior in aqueous mixtures of negatively charged silver nanoparticles (Ag NPs) together with the cationic surfactants cetyltrimethylammonium bromide (CTAB) and dodecyltrimethylammonium chloride (DTAC), respectively, has been investigated using SANS and SAXS. From our SANS data analysis we are able to conclude that the surfactants self-assemble into micellar clusters surrounding the Ag NPs. We are able to quantify our results by means of fitting experimental SANS data with a model based on clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…This is most probably due to the stabilization of the micellar clusters of cationic surfactants by the negatively charged silver nanoparticles. This finding is in agreement with small-angle neutron scattering and small-angle X-ray scattering measurements recently conducted [34] to explain the enhanced colloidal stability of silver nanoparticles in the presence of an oppositely charged surfactant.…”
Section: The Ctab Casesupporting
confidence: 91%
“…This is most probably due to the stabilization of the micellar clusters of cationic surfactants by the negatively charged silver nanoparticles. This finding is in agreement with small-angle neutron scattering and small-angle X-ray scattering measurements recently conducted [34] to explain the enhanced colloidal stability of silver nanoparticles in the presence of an oppositely charged surfactant.…”
Section: The Ctab Casesupporting
confidence: 91%
“…Possibly, stabilizers such as surfactants like cetyltrimethylammonium bromide (CTAB) could be introduced at higher precursor concentrations to further improve the stability and yield of the process. A positively-charged surfactant such as CTAB can create a micelle cluster in the vicinity of negatively-charged AgNPs, averting their aggregation [31]. In comparison with other precursor concentrations, the FWHM values increased considerably at 10 mM, 15 mM and 20 mM, indicating an increase in size polydispersity of the product.…”
Section: Resultsmentioning
confidence: 99%
“…Gao et al reported that the dispersion and stability of Ag NPs mainly attribute to the surface charge [31]. The presence of negatively charged groups improves the stability and dispersion of Ag NPs in aqueous solutions [32].…”
Section: Structural Characterization Of Ag Npsmentioning
confidence: 99%